Professional Guru PAK dalam Perspektif Etis Teologis Kekristenan - Herkulanus Rangga; Reni Triposa; Simatauw, Marfy (ICHTUS: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Abstract: The expertise and professional skills of the teacher, sir, are a teacher's abilities in theteaching and learning process. teacher professional skills also require expertise that is truly possessedby a professional teacher. In learning Christianity, a teacher's professional competence is also verymuch needed, especially in today's increasingly developing era. A Christian Religious educator mustalso have a good personality so that he can be an example for his students as exemplifying JesusChrist. Not only having a good personality but also having a spirituality that is really owned by ateacher of Christianity. As educators, the Christian religion taught must be Bible-centered, whichforms the basis of the material in learning so that what will be delivered is by Bible-centered Christianteachings. The author uses qualitative and descriptive research methods by conducting literaturestudies on this research. So, the professional competence of teachers in the PAK learning process isthe Professional Competence of Teachers in the Learning Process of Christian Religious Education. Sothe journal is about a teacher's professionalism who must have the ability, skills, and expertise inPAK learning which must be Bible-centered.Keywords: teacher's professional expertise and skills; learning process with Christian theology;Christian educationAbstrak: Keahlian dan kecakapan profesional guru pak merupakan kemampuan seorang guru dalamproses belajar mengajar. kecakapan profesional guru juga membutuhkan keahlian yang benar-benaryang dimiliki oleh seorang guru profesional. Proses pembelajaran Agama Kristen kompetensiprofesional seorang guru juga sangat dibutuhkan apalagi pada zaman yang semakin berkembangsaat ini. Seorang pendidik Agama Kristen juga haruslah memiliki kepribadian yang baik sehinggadapat menjadi teladan bagi para peserta didiknya sebagaimana meneladani Yesus Kristus. Bukanhanya memiliki kepribadian baik saja tetapi spiritualitasnya juga haruslah benar-benar dimiliki olehseorang pengajar Agama Kristen. Sebagai pendidik Agama Kristen yang diajarkan haruslah berpusatpada Alkitab yang menjadi dasar materi dalam pembelajaran sehingga apa yang akan disampaikansesuai dengan ajaran Kristen yang berpusat pada Alkitab. Penulis menggunakan metode penelitiankualitatif dan metode deskriptif dengan melakukan studi Pustaka terhadap penelitian ini. Jadi,kecakapan profesional guru dalam proses pembelajaran PAK Kompetensi Profesional Guru dalamProses Pembelajaran Pendidikan Agama Kristen. Jadi Jurnal tentang seorang profesionalisme guruyang harus memiliki kemampuan, keterampilan, dan keahlian dalam pembelajaran PAK yang harusberpusat pada Alkitab.Kata kunci: keahlian dan kecakapan profesional guru; proses pembelajaran dengan teologiskekristenan; pendidikan agama Kristen